Strategi Pemerintahan Xi Jinping terhadap Taiwan dalam Mengamankan Kedaulatan Tingkok - Inneke Firsana Dewi; Karina Utami Dewi (Universitas Muhammadiyah Yogyakarta, 2019)
The dynamics of China and Taiwan relation which began with a civil war between the Communist Party and the Nationalist Party have not ended yet. President Tsai Ing-wen rejected the existence of the One China Policy and continued to strive for Taiwan#39;s independence in various ways. On the contrary, President Xi Jinping firmly declined Taiwan independence and insisted on defending Taiwan position as part of Chinese sovereignty. This paper aims to explain the attempt of Chinese government under President Xi Jinping in responding to Taiwan move using the concept of security sector by Buzan, Waever, and de Wilde encompasses the security strategy of the military, political,and economic sectors. Through the analysis form this concept, Chinese government’s attempt in military and political sector succeeded to overcome the threat from Taiwan position while in the economic sector, the outcome is not as expected since Taiwanese government intended not to depend on Chinese economics.